Cataleptogenic Effect of Haloperidol Formulated in Water-Soluble Calixarene-Based Nanoparticles - Nadezda E. Kashapova; Ruslan R. Kashapov; Albina Y. Ziganshina; Dmitry O. Nikitin; Irina I. Semina; Vadim V. Salnikov; Vitaliy V. Khutoryanskiy; Rouslan I. Moustafine; Lucia Y. Zakharova (MDPI AG, 2023)
In this study, a water-soluble form of haloperidol was obtained by coaggregation with calix[4]resorcinol bearing viologen groups on the upper rim and decyl chains on the lower rim to form vesicular nanoparticles. The formation of nanoparticles is achieved by the spontaneous loading of haloperidol into the hydrophobic domains of aggregates based on this macrocycle. The mucoadhesive and thermosensitive properties of calix[4]resorcinol-haloperidol nanoparticles were established by UV-, fluorescence and CD spectroscopy data. Pharmacological studies have revealed low in vivo toxicity of pure calix[4]resorcinol (LD50 is 540 ± 75 mg/kg for mice and 510 ± 63 mg/kg for rats) and the absence of its effect on the motor activity and psycho-emotional state of mice, which opens up a possibility for its use in the design of effective drug delivery systems. Haloperidol formulated with calix[4]resorcinol exhibits a cataleptogenic effect in rats both when administered intranasally and intraperitoneally. The effect of the intranasal administration of haloperidol with macrocycle in the first 120 min is comparable to the effect of commercial haloperidol, but the duration of catalepsy was shorter by 2.9 and 2.3 times (p < 0.05) at 180 and 240 min, respectively, than that of the control. There was a statistically significant reduction in the cataleptogenic activity at 10 and 30 min after the intraperitoneal injection of haloperidol with calix[4]resorcinol, then there was an increase in the activity by 1.8 times (p < 0.05) at 60 min, and after 120, 180 and 240 min the effect of this haloperidol formulation was at the level of the control sample.